Mapping perception across English and Uzbek: lexical construal, semantic extension, and theoretical implications - Karabayeva , Barno Bobir qizi (The Lingua Spectrum, 2026)
This article examines perception as a structured linguistic category in English and Uzbek. The aim is to identify which theoretical principles explain how perception verbs are organized, contrasted, and extended beyond literal sensory experience. The material consists of a compact contrastive set of verbs drawn from English usage and Uzbek lexicographic sources. Typological comparison, componential analysis, and contextual interpretation were used. The analysis shows that both languages distinguish central experiential and agentive patterns most clearly in vision and audition, while lower modalities distribute lexical meaning in a less symmetrical way. A second result concerns semantic extension: verbs such as see, hear, ko‘rmoq, and eshitmoq regularly move toward understanding, information uptake, stance, and interpersonal management. The article argues that perception in the two languages should be studied through the interaction of bodily grounding, lexical structure, and discourse-based reinterpretation. A limitation is the small data set, so the conclusions are proposed as a theoretical model rather than a frequency map.